Breast cancer genomics and immuno-oncological markers to guide immune therapies. (October 2018) - Hammerl, D.; Smid, M.; Timmermans, A.M.; Sleijfer, S.; Martens, J.W.M.; Debets, R.
Abstract: There is an increasing awareness of the importance of tumor – immune cell interactions to the evolution and therapy responses of breast cancer (BC). Not surprisingly, numerous studies are currently assessing the clinical value of immune modulation for BC patients. However, till now durable clinical responses are only rarely observed. It is important to realize that BC is a heterogeneous disease comprising several histological and molecular subtypes, which cannot be expected to be equally immunogenic and therefore not equally sensitive to single immune therapies. Here we review the characteristics of infiltrating leukocytes in healthy and malignant breast tissue, the prognostic and predictive values of immune cell subsets across different BC subtypes and the various existing immune evasive mechanisms. Furthermore, we describe the presence of certain groups of antigens as putative targets for treatment, evaluate the outcomes of current clinical immunotherapy trials, and finally, we propose a strategy to better implement immuno-oncological markers to guide future immune therapies in BC.